CIAT-CCAFS CSA Profiles in Kenya drove national/county plans, informed US$ 250 million World Bank investment - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
CIAT-CCAFS past work in Kenya, including supporting the development of the Kenya CSA Framework Program and Kenya CSA Profile served formed the technical basis for the development of a US$250 Million World Bank investment in the Kenya CSA Project (KCSAP). CIAT also prepared 24 County Risk Profiles which are now activity being used by the KCSAP and county governments to directly support the development and implementation of the KCSAP, and other county-level agricultural programming.